The potential role of RNA N6-methyladenosine in primary Sjögren’s syndrome - Xiao, Qiufeng; Wu, Xunyao; Deng, Chuiwen; Zhao, Lidan; Peng, Linyi; Zhou, Jiaxin; Zhang, Wen; Zhao, Yan; Fei, Yunyun (Frontiers in Medicine, 2022)
Introduction: Primary Sjögren's syndrome (pSS) is a common chronic systemic autoimmune disease, which is characterized by lymphoid infiltration and progressive destructions of the exocrine glands. N6-methyladenosine (m6A) RNA modification is considered the most common, abundant, and conserved internal transcript modification. m6A is associated with multiple diseases such as obesity, infertility, cancer, rheumatoid arthritis, and systemic lupus erythematosus. However, no study has investigated the role of m6A in pSS. Materials and Methods: 44 patients diagnosed with pSS and 50 age-and sex-matched healthy controls were enrolled in this study. We detected the mRNA levels of METTL3, WTAP, RBM15, FTO, ALKBH5, YTHDF1, YTHDF2, YTHDF3, YTHDC1, YTHDC2, ISG15, and USP18 in peripheral blood from pSS patients and healthy controls. The clinical features and laboratory findings of pSS, including ESR, CRP, C3, C4, IgG, IgA, IgM, RF, anti-SSA antibody, anti-SSB antibody, ANA, WBC, RBC, HGB, PLT, lymphocyte, lymphocyte%, monocyte, monocyte%, neutrophil, neutrophil %, duration, and ESSDAI scores were collected. Results: The mRNA levels of m6A writers (METTL3 and RBM15), erasers (ALKBH5 and FTO), and readers (YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2) were all significantly increased in peripheral blood from pSS patients. The expression of METTL3, RBM15, FTO, YTHDF1, YTHDF2, YTHDC1, and YTHDC2 was all correlated with CRP and might indicate the disease activity of pSS. In addition, FTO, YTHDC1, and YTHDC2 were associated with WBC, N, L, and M. Multivariate logistic regression analysis showed that an increased mRNA level of ALKBH5 was a risk factor for pSS. The mRNA level of ISG15 had correlations with those of FTO, YTHDF2, YTHDF3, and YTHDC2. Conclusions: The mRNA levels of m6A writers, erasers, and readers were all significantly increased in PBMCs from pSS patients. m6A elements correlating with clinical variables may indicate the disease activity and inflammation status of pSS. Increased ALKBH5 was a risk factor for pSS. Our results also indicated that m6A modification might regulate the ISG15 pathway and play an active role in the pathogenesis of pSS.